Asuhan Kebidanan Komprehensif untuk Meningkatkan Kesehatan Ibu dan Bayi: Studi Kasus di Klinik Pratama Shaqi - Widya Ayu Wulandari; Nining Tunggal Sri Sunarti (STIKes Ibnu Sina Ajibarang, 2025)
Comprehensive midwifery care is a comprehensive service provided by midwives that covers all stages of a woman's reproductive life, from pregnancy, childbirth, newborn care, postpartum, to the provision of contraceptive services. This service aims to detect potential risks that can occur in pregnant women and newborns early, so that the care provided can reduce complications and improve the safety of mothers and children. In this study, comprehensive midwifery care was provided to Mrs. R, starting from pregnancy to the neonatal phase, using a case study method. The data used consisted of primary data collected through direct observation, interviews with patients, and secondary data obtained from reviewing the patient's medical documents. The implementation of care was carried out in accordance with the 10T standards, which are guidelines for providing quality midwifery services. The results of the assessment indicated that Mrs. R was at high risk of developing preeclampsia because the gap between her pregnancies and her first child reached 11 years. In the third trimester, Mrs. R complained of back pain and shortness of breath, which indicated a potential risk that required more attention. Therefore, midwifery care provided must include more intensive examinations and appropriate actions. Antenatal care is provided starting at 38 weeks of gestation and continuing until 39 weeks and 2 days, with regular monitoring of the condition of the mother and fetus. The process of labor, newborn care, the postpartum period, and the neonatal phase occurs physiologically and in accordance with midwifery guidelines. This final project report was prepared using Varney's 7-step midwifery management approach, which includes assessment, planning, implementation, and evaluation of care, and documented using the SOAP format (Subjective, Objective, Assessment, and Plan), to provide a clear and structured picture of the midwifery care provided.